An example of coworking and smart living in Milan - Liala Baiardi (Agathón)
The article focuses on the modern formats of working space use deriving from the sharing economy. The short rent, created mainly to cope with residential needs, has in fact recently seen the development of increasingly growing demand for shared and temporary work spaces. A brief description of the developments of the last century introduces the analysis aimed at investigating the characteristics of the main temporary use methods.  Also illustrates the example of smart living design Eco System Temporary House.